8
$\begingroup$

The classic example... $X \sim Po\left (\lambda\right ), Y \sim Po\left (\mu\right)$, X and Y are independent. Show that the conditional distribution of X is binomially distributed. Or in other words, $P(X=k\mid X+Y = n) = P (\tilde{X} = k), \tilde{X} \sim B\left (\frac{\lambda}{p} ,\frac{\lambda}{n}\right )$.

I've so far managed to reach to this step, and have been stuck since. Just somehow gotta get a $\frac{1}{n!}$ in the denominator, that would then complete the proof..or at least I think..

$$P(X=k\mid X+Y=n) = \frac{\frac{\lambda^{k}\mu^{n-k}}{k!(n-k)!}}{P(X+Y = n)}= \frac{\frac{\lambda^{k}\mu^{n-k}}{k!(n-k)!}}{\sum_{i=1}^{n} \frac{\lambda^{i}\mu^{n-i}}{i!(n-i)!}}$$

Thanks for the help!

$\endgroup$
  • $\begingroup$ The summation in the denominator must run from $i=0$ to $n$. $\endgroup$ – user17762 May 29 '12 at 19:50
  • $\begingroup$ There is a typo, you wrote $B\left (\frac{\lambda}{p} ,\frac{\lambda}{n}\right )$. Presumably you mean something like $B\left(\frac{\lambda}{\lambda+\mu},n\right)$. $\endgroup$ – André Nicolas May 29 '12 at 20:18
  • $\begingroup$ @AndréNicolas did you mean the other way around? Isn't it represented in B(n,p)? And yep thanks for the correction! I thought the probability and n were just merely derived from the $\lambda$ without considering the $\mu$. Makes more sense now anyway! $\endgroup$ – mercurial May 30 '12 at 6:19
  • $\begingroup$ Sure. Binomial $n$ trials prob. of success each trial $\frac{\lambda}{\lambda+\mu}$. $\endgroup$ – André Nicolas May 30 '12 at 12:30
8
$\begingroup$

HINT

Remember that $$\sum_{i=0}^{n} \binom{n}{i} \lambda^i \mu^{n-i} = \left( \lambda + \mu\right)^n$$ The above gives us that $$\sum_{i=0}^{n} \dfrac{n!}{i! (n-i)!} \lambda^i \mu^{n-i} = \left( \lambda + \mu\right)^n$$ which inturn gives us that $$\sum_{i=0}^{n} \dfrac{ \lambda^i \mu^{n-i}}{i! (n-i)!} = \dfrac{\left( \lambda + \mu\right)^n}{n!}$$

$\endgroup$
0
$\begingroup$

Instead of using the summation in the denominator to calculate $P(X+Y=n)$, we might use the property that the sum of two independent Poisson distributions is a Poisson distribution, whose parameter is the sum of the parameters of two independent Poisson (can be shown using mgf; see Theorem 3.2.1 in Introduction to Mathematical Statistics by Hogg et al.). Therefore $P(X+Y=n)=\frac{1}{n!}(\lambda+\mu)^ne^{-(\lambda+\mu)}$, which can be plugged into the denominator of last expression.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.